2019
DOI: 10.1016/j.ebiom.2019.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Specific loss of adipocyte CD248 improves metabolic health via reduced white adipose tissue hypoxia, fibrosis and inflammation

Abstract: Background: A positive energy balance promotes white adipose tissue (WAT) expansion which is characterized by activation of a repertoire of events including hypoxia, inflammation and extracellular matrix remodelling. The transmembrane glycoprotein CD248 has been implicated in all these processes in different malignant and inflammatory diseases but its potential impact in WAT and metabolic disease has not been explored. Methods: The role of CD248 in adipocyte function and glucose metabolism was evaluated by omi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 41 publications
4
54
1
Order By: Relevance
“…A recent study has reported that the transmembrane glycoprotein CD248 affects several pathways related to hypoxia in adipocytes and modulates the vascularity of WAT, establishing a link between the lack of oxygen and angiogenesis. They also observed an increase in CD248 expression in human white adipocytes that was positively associated with obesity and metabolic complications [159].…”
Section: Extracellular Matrix Remodeling Of Adipose Tissue In Obesmentioning
confidence: 99%
“…A recent study has reported that the transmembrane glycoprotein CD248 affects several pathways related to hypoxia in adipocytes and modulates the vascularity of WAT, establishing a link between the lack of oxygen and angiogenesis. They also observed an increase in CD248 expression in human white adipocytes that was positively associated with obesity and metabolic complications [159].…”
Section: Extracellular Matrix Remodeling Of Adipose Tissue In Obesmentioning
confidence: 99%
“…Although the mechanisms involved are not fully understood, hypoxia is known to increase adipose expression of the transcriptional factor hypoxia inducible factor-1α (HIF-1α), which can induce inflammation, fibrosis and IR in rodent WAT [ 56 , 57 , 58 ]. Possibly related are the recently observed associations of CD248 with adipose tissue hypoxia, inflammation, and fibrosis [ 59 ]. CD248 is a sensing transmembrane glycoprotein that is highly expressed in WAT of individuals with obesity, IR and diabetes, and reduced after bariatric surgery [ 59 ].…”
Section: Healthy and Unhealthy Responses Of Adipose Tissue To Excementioning
confidence: 99%
“…Possibly related are the recently observed associations of CD248 with adipose tissue hypoxia, inflammation, and fibrosis [ 59 ]. CD248 is a sensing transmembrane glycoprotein that is highly expressed in WAT of individuals with obesity, IR and diabetes, and reduced after bariatric surgery [ 59 ]. In human adipocytes, in vitro knock down of CD248 by siRNA attenuated hypoxia-induced HIF-1α promoter activity, as well as the expression of a whole cluster of hypoxia-induced genes.…”
Section: Healthy and Unhealthy Responses Of Adipose Tissue To Excementioning
confidence: 99%
See 1 more Smart Citation
“…CD248 (Endosialin/Tumour Endothelial Marker 1) is a transmembrane glycoprotein expressed widely by stromal cells including pericytes (Tomkowicz et al 2010 ; Naylor et al 2014 ), fibroblasts (MacFadyen et al 2005 ), osteoblasts (Naylor et al 2012 ) and adipocytes (Petrus et al 2019 ). CD248 expression is high on all mesenchymal cells in embryonic and new-born tissues but is expressed at very low levels postnatally in normal tissue (Rupp et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%